Genetic diversity of mud crab (Scylla paramamosain) in Vietnam based on cox1 gene fragments - LE TAN PHAT; HOANG TAN QUANG; NGUYEN VAN HUY; MAC NHU BINH; TON THAT CHAT (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Phat LT, Quang HT, Huy NV, Binh MN, Chat TT. 2024. Genetic diversity of mud crab (Scylla paramamosain) in Vietnam based on cox1 gene fragments. Biodiversitas 25: 4379-4388. Mud crab (Scylla paramamosain Estampador 1950) is a commonly found resource throughout Vietnam, with increasing exports each year. However, production is yet to be able to meet consumer demand, which continues to increase, leading to consistently high market prices. Accurately estimating genetic variation in mud crab populations is crucial for developing conservation management strategies for highly exploited fishery resources. In this study, genetic variations and population structure of S. paramamosain were examined by analyzing the nucleotide sequences of a 780 base pairs (bp) region of the mitochondrial cox1 gene from three populations across thirteen collection sites in Vietnam, covering a diverse geographical range. A total of 45 individuals were examined, the cox1 gene sequences were aligned, and 17 haplotypes were identified, with two of these haplotypes being shared by the populations. The haplotype diversity ranged from 0.57143 (Thua Thien Hue) to 0.80000 (Ca Mau). The haplotype network displayed that the haplotypes were divided into two clusters with Hap_3 as the center. Pairwise Fst values between populations ranged low, from 0-0.01266. The AMOVA results highlighted that within-population variation (99.85%) was higher than among-population variation (0.15%). Findings from neutral tests and mismatch analysis suggested implications for mud crab population dynamics. S. paramamosain in Vietnam showed high genetic diversity within the populations, as shown by low genetic variation and the significant gene flow between populations when analyzing the cox1 gene. These results underscore the interconnectedness of the mud crab population and provide a foundation for establishing an enduring mud crab farming initiative in Vietnam.